Inflammasomes and Their Role in Innate Immunity of Sexually Transmitted Infections - Verma, Vivek; Dhanda, Rakesh Singh; Møller, Niels Frimodt; Yadav, Manisha (Frontiers in Immunology, 2016)
Inflammasomes are multiprotein complexes present in the cytosol as Pattern Recognition Receptors (PRRs) or as sensors of Damage Associated Molecular Patterns (DAMPs). After recognition of Microbe Associated Molecular Patterns (MAMPs) or host derived danger signals, Nucleotide oligomerization domain (NOD) like receptors oligomerize to form inflammasomes. The activation of inflammasomes results in an alarm, which is raised to alert adjacent cells through the processing and release of a number of other substrates present in the cytosol. A wide array of inflammasomes and their adapter molecules have been identified in the host’s innate immune system in response to a variety of pathogens. Components of specific pathogens activate different inflammasomes, which once activated in response to pathogen-induced infection, induce the activation of caspases and the release of mature forms of interleukin-1β (IL-1β) and IL-18. Identifying the mechanisms underlying pathogen-induced inflammasome activation is important if we are to develop novel therapeutic strategies to target STI related pathogens. This information is currently lacking in literature. In this review, we have discussed the role of various inflammasomes in sensing different sexually transmitted infections, as well as the beneficial or detrimental effects of inflammasome signaling in host resistance. Additionally we have discussed both canonical and noncanonical processing of IL-1β induced with respect to particular infections. Overall, these findings transform our understanding of both the basic biology and clinical relevance of inflammasomes.